The Effects of Spiral Taping Treatment on Temporomandibular Disorder - Choi Bo-Hee; Hwang Jae-Ok; Seo Jung-chul (Korean Pharmacopuncture Institute, 2006)
Objective : The purpose of this study is to estimate the effects of spiral taping treatment on temporomandibular disorder. Methods : 22 temporomandibular disorder patients were treated with spiral taping, and no other treatments such as herbal medicine, acupuncture, herbal acupuncture, and chiropractic therapy were added. We evaluated the improvement by temporomandibular pain and mouth opening range. Results : 11 patients felt no pain or inconvenience of daily life and 4 patients showed improvement of pain or symptom after 1 month of spiral taping theraphy. 3 patients had normal opening size of mouth and convenience of daily life, and 2 patient showed improvement of opening size of mouth as 35mm-40mm after 1 month of spiral taping theraphy. Conclusions : These results suggest spiral taping treatments contribute to the improvement of temporomandibular disorders. Further study is needed for the confirmation of this effect of spiral taping treatments on temporomandibular disorders.